2020
DOI: 10.1111/ecog.04972
|View full text |Cite
|
Sign up to set email alerts
|

Elevation filters seed traits and germination strategies in the eastern Tibetan Plateau

Abstract: Seeds are the colonizing propagules for many plants and may therefore contribute to the filtering of species during the process of colonization and community assembly. Environmental filtering of seed traits may occur among species and influence community composition, or within species and influence the environmental breadth that a given species inhabits. To test for evidence of such filtering of seed traits, we measured morphological and germination traits of seeds of 408 angiosperm species collected across an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 92 publications
(136 reference statements)
2
10
0
Order By: Relevance
“…Multiple biologists have argued that we must begin to examine how populations within species vary genetically across geographic and environmental gradients [24,60,63]. This requires taking advantage of experimental designs that focus specifically on characterizing the genetic control of seed traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple biologists have argued that we must begin to examine how populations within species vary genetically across geographic and environmental gradients [24,60,63]. This requires taking advantage of experimental designs that focus specifically on characterizing the genetic control of seed traits.…”
Section: Discussionmentioning
confidence: 99%
“…In others, mass increases poleward [33,40,[42][43][44][45][46][47][48][49], and with increasing altitude [30,[50][51][52][53] or shows no geographic trend [32,33,[54][55][56][57][58][59]. Geographic patterns in temperature requirements for germination and germination rate are equally diverse [36,51,53,[60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…However, our study revealed a recent pattern of adaptation toward lighter seed mass in highland forests, independent of phylogenetic information (Figure 2e), indicating convergence in SM values toward higher altitude conditions. Past evolution and phylogenetic history determine seed mass (Wang et al, 2021), which affects the ability of lineages to colonize sites or persist under different environmental conditions.…”
Section: Trait Composition Patternsmentioning
confidence: 99%
“…Seeds are believed to be smaller and more elongated, with a larger surface area at higher altitudes ( Bu et al., 2007 ; Qi et al., 2014 ). Some studies believe that this greater surface area is conducive to faster germination, highlighting the direct influence of seed morphology on germination ( Ruprecht et al., 2015 ; Wang et al., 2021 ). However, the veracity of these claims is still under debate.…”
Section: Introductionmentioning
confidence: 99%